A study on the barriers to lean manufacturing implementation for small-scale industries in Himachal region (India). (15th July 2019) - Jamwal, Anbesh; Aggarwal, Ankur; Gupta, Sumit; Sharma, Parul
In today's competitive market, lean philosophy has a vital role to play which is mainly governed by a reduction in cost, ameliorated quality, and higher expectations of customers as well as superior productivity. It has been globally witnessed that the companies which implement lean manufacturing in their system result in improved productivity and better customer satisfaction, along with the cost reduction. Lean manufacturing is the most important productivity improvement tool. The aim of this research is to identification and confirmation of the barriers to lean implementation in small-scale industries in the Himachal region (India) and to build up a relationship between the barriers. A total interpretive structural modelling approach is applied to identify the relationship of various barriers. It is evident from the research that the cost of facilities is a major barrier to implementing lean in the small-scale industries. However, the government gives the financial support for the small-scale industries in Himachal Pradesh.